The paradigm of the investment development path : does it holds for Portugal? Evidence for the period 1990-2011 - Fonseca, Miguel (2016)
The main goal of this paper is to discuss the validity of the Investment Development Path Hypothesis for Portugal, with reference to the historical period 1960-2011. Looking at the transformations that took place in the world economy in the last quarter of the 20th century, as a result of liberalization, deregulation and market opening process, one of the most striking features was the emergence of multinational enterprises in all sectors and countries of the world. Consequently, the Foreign Direct Investment flows promoted by these firms have grown significantly, even faster than world trade and world output, in the same period. According to the Investment Development Path (IDP) theory there is a dynamic and intertemporal relationship between an economy’s level of development and the country's inward and outward investment position. In this paper we estimate this hypothesis for Portugal and other 28 countries in different stages of development, for the period 1990-2011 at an aggregate level. We use fixed- effects panel data models and generally our research´s results provide support to the IDP theoretical paradigm, although we couldn’t capture all the stages predicted, given the lack of heterogeneity between the most countries of our sample and also the relatively short time period considered.